PENEGAKAN HUKUM TERHADAP PEREDARAN PAKAIAN BEKAS IMPOR DI INDONESIA - David Arnoldus Soritua (2024)
Nowadays, imported second-hand clothes are in great demand among the public and teenagers who follow modern clothing styles. In Indonesia, imported used clothing is considered illegal goods because it does not comply with applicable laws and regulations. The increasing interest in thrifting goods imported from abroad has prompted the Minister of Trade to issue regulations regarding goods that are prohibited from exporting and goods that are prohibited from importing, as regulated in Minister of Trade Regulation Number 40 of 2022 concerning Amendments to Minister of Trade Regulation Number 18 of 2021. There are also laws Law No. 7 of 2014 which discusses trade. Covers domestic and foreign trade. The type of research in this writing is normative juridical by observing legal developments in the literature which is carried out by understanding library sources. The aim of this research is to determine the legal basis, regulations, and effectiveness of government policies regarding the prohibition of imports of used clothing, and to determine the implementation of law enforcement that can be applied by the Government regarding the distribution of imported used clothing. Some of the efforts made by the Ministry of Trade of the Republic of Indonesia are supervision, namely by tightening the inflow of imported goods, to protect domestic industry by building synergy between stakeholders, taking action by collaborating between the Ministry of Trade, the Directorate General of Customs and Excise (DJBC), TNI, Polri, Bakamla, Provincial Government and Regional Government, as well as Review of Regulations by reviewing related laws and regulations, to be able to adjust and increase the effectiveness of these regulations.